Standardization of patch budding in Jack fruit (Artocarpus heterophyllus Lam.) - Fathimath Sherin Shasna K.K (Department of Pomology, College of Agriculture, 2019)
The present investigation entitled ‘Standardization of patch budding in jack fruit (Artocarpus heterophyllus Lam.) was undertaken at the College of Agriculture, Padannakkad, Kasaragod during the period 2018 June to 2019 June . The research work was carried out to assess the effect of seed treatments on the seedling growth to attain the buddable size and seasonal influence on the success of patch budding. The first experiment was laid out in CRD with seven treatments and three replications. Seeds were subjected to different treatments such as gibberellic acid 100 ppm (T1) and 200 ppm (T2), potassium chloride 0.5 per cent (T3) and 1 per cent (T4), potassium nitrate 1 per cent (T5) and water (T6) for one day before sowing. In treatment T7 (control), the seeds were sown without any treatment. The treatment T5 took minimum number of days for germination (17 days) which was on par with T1 (17.33 days) and maximum number of days (26.70 days) required for sprouting was observed in control. T5 recorded minimum days (23.47 days) to attain 50 per cent germination (30.62 % reduction over control) followed by T1 (25.33 days). Maximum germination percentage and germination rate was obtained T1 (82.22 %, 0.59) which was on par with the treatment T2 (80.16 %, 0.53) and T5 (78.44 %, 0.57). Maximum number of leaves were produced in T5 (4.17), which was on par with T4 (3.6). Maximum shoot length was observed in T1 (28.20 cm) at 60 DAS. At 90 DAS, the treatment T1 (46.11 cm) recorded maximum shoot length which was on par with T2 (43.11 cm). Maximum girth (2.09 cm) was observed in T1 which was on par with T2 (2.04 cm) and T5 (1.96 cm) at 60 DAS. The maximum seedling vigour was obtained in T1 (2319.33, 3788.15) which was on par with T2 (2129.80, 3503.94) followed by T5 (2029.56, 3075.45) at 60 and 90 DAS respectively. Results of the study revealed that seed priming with chemicals have significant effect on growth and vigour of the seedling. Maximum desirable 2